Urine Biomarkers for Prostate Cancer Diagnosis and Progression - Jeremy Clark, Rachel Hurst, Mark Simon Winterbone, Hardev Pandha, Antoinette Perry, Sophie McGrath, Richard Morgan, Adele E Connor, Asia C Jordan, Deirdre Winrow, Colin Cooper (Société Internationale d’Urologie Journal)
Prostate cancer (PCa) can be highly heterogeneous and multifocal, and accurate assessment of the volume, grade, and stage of PCa in situ is not a simple task. Urine has been investigated as a source of PCa biomarkers for over 70 years, and there is now strong evidence that analysis of urine could provide more accurate diagnosis and a better risk stratification that could aid clinical decisions regarding disease surveillance and treatment. Urine diagnostics is a developing area, moving towards multi-omic biomarker integration for improved diagnostic performance. Urine tests developed by strong collaborations between scientists and clinicians have the potential to provide targeted and meaningful data that can guide treatment and improve men’s lives.